Chapter 3 National Myths and Language Status in Early Modern Wales and Brittany - Bennett, Karen; Cattaneo, Angelo (Taylor & Francis, 2022)
This chapter explores how the revision of national myths in Early Modern Britain and France reflects conflicts and contradictions between the perspectives of the dominant nations, England and France, and those of two subordinate nations, Wales and Brittany, formally annexed by their larger neighbours in the 16th century, and how the national myths in turn impinged on the status of the vernacular languages of the subordinate nations, Welsh and Breton. In order to legitimise the new Church of England, English protestant apologists claimed that its protestant faith was the continuation of the pure faith of the Early Church, which the ancient Britons, ancestors of the Welsh, had acquired directly from a disciple of Christ. Richard Davies' preface to the 1567 Welsh New Testament, however, re-appropriated the narrative as specifically Welsh. Davies' narrative was influential in Wales and contributed to a cultural context, together with the Welsh Bible translation, in which the Welsh language could flourish despite the increasing dominance of English. In the case of Brittany and France, the paper explores the contradiction between the antiquarian prestige conferred upon Breton by contemporary language antiquity myths and its actual subordinate sociolinguistic status vis-a-vis French.